THE INFLUENCE OF SYSTEM QUALITY, INFORMATION QUALITY, SERVICE QUALITY AND COMPUTER ANXIETY ON USER SATISFACTION IN THE DANA APPLICATION - Fatmawati, Erina Farah; Fitriati, Azmi; Fakhruddin, Iwan; Pandansari, Tiara (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to determine the influence of system quality, information quality, services quality and computer anxiety on user satisfaction of dana application. Sampling in this research used to Accidental Sampling technique with a sample size of 100 respondents who used the dana application. The analytical method used is Structural Equation Modeling (SEM) with a Partial; Least Square (PLS) approach. The research results show that system quality and service quality have a positive effect on dana application user satisfaction. Meanwhile, information quality and computer anxiety have no effect on user satisfaction with dana application.